2010
DOI: 10.4103/1742-6413.62257
|View full text |Cite
|
Sign up to set email alerts
|

Fine needle aspiration biopsy diagnosis of dedifferentiated liposarcoma: Cytomorphology and MDM2 amplification by FISH

Abstract: Lipomatous mesenchymal tumors constitute the most common type of soft tissue tumors. Well-differentiated liposarcoma (WDLS) can undergo dedifferentiation to a nonlipogenic sarcoma of variable histologic grade. In the recent literature, amplification of the murine double minute 2 (MDM2) oncogene, which has a role in cell cycle control, has been successful in distinguishing WDLS from benign lesions. We present a case of dedifferentiated liposarcoma diagnosed by fine-needle aspiration (FNA), using cytomorphology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…MDM2 FISH also is used to provide support for the diagnosis of dedifferentiated liposarcoma when the well differentiated component is not sampled. Recently, the feasibility of using MDM2 FISH in FNA smears was demonstrated for the diagnosis of dedifferentiated liposarcoma 66…”
Section: Introductionmentioning
confidence: 99%
“…MDM2 FISH also is used to provide support for the diagnosis of dedifferentiated liposarcoma when the well differentiated component is not sampled. Recently, the feasibility of using MDM2 FISH in FNA smears was demonstrated for the diagnosis of dedifferentiated liposarcoma 66…”
Section: Introductionmentioning
confidence: 99%
“…Well-differentiated liposarcoma (WDLS), which is the mostcommonsubtypeofliposarcoma,canproducemetastases with bone destruction [1]. I read with great interest the articlebyMystakidouandcolleagues [2].IwouldliketocompletethediscussionofMystakidouandcolleaguesbyintroducing a major route by which zoledronic acid could influence bonemetastasesofliposarcoma.…”
Section: Deareditormentioning
confidence: 98%
“…Recent histopathologic findings revealed areas with sheets of osteoclast-type giant cells in the metastatic foci of WDLS [1]. Fusion of the cell membrane of preosteoclasts is anessentialinitialstepinosteoclastmaturation.Cholesterol in the membranes of preosteoclasts has a major role in the osteoclast-like cell formation via cellular membrane fusion…”
Section: Deareditormentioning
confidence: 99%
“…Whereas most reported DDLPS cases were recognized in light of a concurrent or prior history of WDLPS, in approximately half of the cases of PLPS the authors initially favored other diagnostic possibilities, including poorly differentiated carcinoma and high-grade sarcoma without specifying the line of differentiation. [24][25][26][27] In this study, we analyze the cytologic aspirates of 38 histologically confirmed high-grade liposarcomas, including 25 DDLPS and 13 PLPS, correlating the cytomorphology with clinical, histologic, immunohistochemical, and genetic data.…”
Section: Introductionmentioning
confidence: 99%